Effects of soil pollutants, biogeochemistry and microbiology on the distribution and composition of enchytraeid communities in urban and suburban holm oak stands - Rota, Emilia; Caruso, Tancredi; Monaci, Fabrizio; Baldantoni, Daniela; De Nicola, Flavia; Iovieno, Paola; Bargagli, Roberto (Environmental Pollution, 2013)
Holm oaks form typical urban woodlands in the Mediterranean region. We aimed at characterizing the enchytraeid communities in these environments and searching for possible correlations with soil pa- rameters, including the traffic contamination. Samples of litter and topsoil were collected at different spatial scales and seasons in Naples and Siena cities and in two suburban stands. Only the co-variation between pollution and other soil chemico-physical factors showed significant effects, whereas no direct effect of soil microbiology was detected. Some thermophilous Fridericia and Achaeta tolerate high con- centrations of heavy metals and PAHs and their abundance was mainly determined by Ca bioavailability. Central-European mesophilous species increased significantly under more temperate environmental conditions. Different combinations of soil cohesiveness, grain size composition and moisture regime seem to select species of certain body sizes. 
The following values have no corresponding Zotero field: publisher: Elsevier Ltd
Keywords: Enchytraeids; Mediterranean urban communities; Microbiology; Pollutants; Soil biogeochemistry; terrestrial annelids

Effects of soil pollutants, biogeochemistry and microbiology on the distribution and composition of enchytraeid communities in urban and suburban holm oak stands - Rota, Emilia; Caruso, Tancredi; Monaci, Fabrizio; Baldantoni, Daniela; De Nicola, Flavia; Iovieno, Paola; Bargagli, Roberto (Environmental Pollution, 2013)
Holm oaks form typical urban woodlands in the Mediterranean region. We aimed at characterizing the enchytraeid communities in these environments and searching for possible correlations with soil pa- rameters, including the traffic contamination. Samples of litter and topsoil were collected at different spatial scales and seasons in Naples and Siena cities and in two suburban stands. Only the co-variation between pollution and other soil chemico-physical factors showed significant effects, whereas no direct effect of soil microbiology was detected. Some thermophilous Fridericia and Achaeta tolerate high con- centrations of heavy metals and PAHs and their abundance was mainly determined by Ca bioavailability. Central-European mesophilous species increased significantly under more temperate environmental conditions. Different combinations of soil cohesiveness, grain size composition and moisture regime seem to select species of certain body sizes. 
Keywords: Enchytraeids; Mediterranean urban communities; Microbiology; Pollutants; Soil biogeochemistry; terrestrial annelids

Holm Oak (Quercus ilex L.) canopy as interceptor of airborne trace elements and their accumulation in the litter and topsoil - Fantozzi, Federica; Monaci, Fabrizio; Blanusa, Tijana; Bargagli, Roberto (ENVIRONMENTAL POLLUTION, 2013)
We investigated the role of urban Holm Oak (Quercus ilex L.) trees as an airborne metal accumulators and metals' environmental fate. Analyses confirmed Pb, Cd, Cu and Zn as a main contaminants in Siena's urban environment; only Pb concentrations decreased significantly compared to earlier surveys. Additionally, we determined chemical composition of tree leaves, litter and topsoil (underneath/outside tree crown) in urban and extra-urban oak stands. Most notably, litter in urban samples collected outside the canopy had significantly lower concentrations of organic matter and higher concentrations of Pb, Cu, Cd and Zn than litter collected underneath the canopy. There was a greater metals' accumulation in topsoil, in samples collected under the tree canopy and especially near the trunk ('stemflow area'). Thus, in urban ecosystems the Holm Oak stands likely increase the soil capability to bind metals. (C) 2012 Elsevier Ltd. All rights reserved.
The following values have no corresponding Zotero field: pub-location: THE BOULEVARD, LANGFORD LANE, KIDLINGTON, OXFORD OX5 1GB, OXON, ENGLAND publisher: ELSEVIER SCI LTD
Keywords: Airborne metals; leaves; Leaves litter; Quercus ilex; Topsoil; Urban environment